2005
DOI: 10.1103/physrevb.72.144101
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of epitaxial strain in perovskites

Abstract: Using an extension of a first-principles method developed by King-Smith and Vanderbilt [Phys. Rev. B 49, 5828 (1994)], we investigate the effects of in-plane epitaxial strain on the groundstate structure and polarization of eight perovskite oxides: BaTiO3, SrTiO3, CaTiO3, KNbO3, NaNbO3, PbTiO3, PbZrO3, and BaZrO3. In addition, we investigate the effects of a nonzero normal stress. The results are shown to be useful in predicting the structure and polarization of perovskite oxide thin films and superlattices.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
245
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(270 citation statements)
references
References 30 publications
20
245
0
1
Order By: Relevance
“…1b, the Landau Devonshire approach predicted an aa phase in that region of the phase diagram 31 . This is the same ground state as found for pure PbTiO 3 under tensile strain 25,28 . However, in both cases, domain formation was neglected.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…1b, the Landau Devonshire approach predicted an aa phase in that region of the phase diagram 31 . This is the same ground state as found for pure PbTiO 3 under tensile strain 25,28 . However, in both cases, domain formation was neglected.…”
Section: Resultssupporting
confidence: 71%
“…Intensive theoretical work has thus been conducted on several ferroelectric materials in order to predict the changes of ferroelectric domain structures induced by strain [24][25][26][27][28][29] . Experimentally, epitaxial strain is typically created by growing high-quality thin films on suitable substrates 30 .…”
mentioning
confidence: 99%
“…Under tensile strain (η > 0) below the paraelectric transition temperature, with corresponding substrate lattice parameters a s > a 0 , the polarisation is oriented parallel to the substrate interface [29,30]. Domains form with ordered regions polarised along the a and b principle axes separated via 90 • domain walls ( Figure 2a).…”
Section: Aa Domainsmentioning
confidence: 99%
“…The observed P 4mm → Amm2 phase transition in PbTiO 3 is in agreement with previous computational results obtained with comparable DFT-based approaches. 41,42 At variance, in SnTiO 3 , the Cm state persists for a wide range of tensile strains with no traces of Amm2 phase observed even for relatively large biaxial tensions. 40 It is noteworthy that both of the representative (stress-free) tensile phases in PbTiO 3 have rather similar structural parameters and are close to each other in energy, the Amm2 state being only 2 meV lower than the Cm one, while, in SnTiO 3 we see much stronger variations in the relative energies (∼20 meV) and structural parameters of the involved polar phases.…”
Section: P 4mmmentioning
confidence: 99%
“…We also demonstrated that, although the stress-free ground state of polar-perovskite SnTiO 3 is the same as that of PbTiO 3 [i.e., tetragonal, with space group P 4mm and spontaneous polarization P ∼ (0, 0, c)], under biaxial tension, the former compound undergoes a transition into a monoclinic Cm phase, P ∼ (a, a, c), while the latter transitions to the Amm2 phase, P ∼ (a, a, 0). 41,42 All of the aforementioned structures, together with the nonpolar cubic P m3m aristotype, are depicted in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%